2003
DOI: 10.1074/jbc.m305826200
|View full text |Cite
|
Sign up to set email alerts
|

A Single Amino Acid Change (Substitution of the Conserved Glu-590 with Alanine) in the C-terminal Domain of Rat Liver Carnitine Palmitoyltransferase I Increases its Malonyl-CoA Sensitivity Close to That Observed with the Muscle Isoform of the Enzyme

Abstract: Carnitine palmitoyltransferase I (CPTI) catalyzes the conversion of long-chain fatty acyl-CoAs to acylcarnitines in the presence of L-carnitine. To determine the role of the highly conserved C-terminal glutamate residue, Glu-590, on catalysis and malonyl-CoA sensitivity, we separately changed the residue to alanine, lysine, glutamine, and aspartate. Substitution of Glu-590 with aspartate, a negatively charged amino acid with only one methyl group less than the glutamate residue in the wild-type enzyme, resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
(63 reference statements)
1
8
0
Order By: Relevance
“…The importance of this region is confirmed by the finding that the intrinsically less malonylCoA-sensitive isoform L-CPT-1 displays a marked increase in inhibition by malonyl-CoA on introduction of a single point mutation, Glu590Ala [77]. Both Glu590 and Met593 are part of strand b13, which lines the entrance to the active site via the CoA site.…”
Section: Substances That Modify Cpt-activitysupporting
confidence: 54%
“…The importance of this region is confirmed by the finding that the intrinsically less malonylCoA-sensitive isoform L-CPT-1 displays a marked increase in inhibition by malonyl-CoA on introduction of a single point mutation, Glu590Ala [77]. Both Glu590 and Met593 are part of strand b13, which lines the entrance to the active site via the CoA site.…”
Section: Substances That Modify Cpt-activitysupporting
confidence: 54%
“…Thus, in the rat liver enzyme, residues Glu-590, Arg-601, Glu-603, and Arg-606 are involved both in catalysis and malonyl-CoA sensitivity as mutations on these sites affect both properties , Napal et al, 2003. The above residues are conserved in the sea bream CPT1 (Glu-588, Arg-599, Glu-601, and Arg-604, respectively in Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Between the cytosolic domains are two transmembrane regions and a short intramitochondrial loop (Fraser et al, 1997;Zammit, 1999). Malonyl CoA binding and inhibition of both CPT-1␣ and CPT-1␤ can be disrupted by deletions or point mutations in both the short N terminus and the C-terminal catalytic domain 1 (Cohen et al, 1998;Swanson et al, 1998;Jackson et al, 2000;Shi et al, 2000;Napal et al, 2003). Interestingly, Zammit and colleagues have shown that deletions within the N-terminal region can actually increase sensitivity of CPT-1␣ to inhibition by malonyl CoA (Jackson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%